2017
DOI: 10.1016/j.joa.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Current use of direct oral anticoagulants for atrial fibrillation in Japan: Findings from the SAKURA AF Registry

Abstract: BackgroundLarge-scale investigations on the use of oral anticoagulants including direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) have not included Japanese patients.MethodsWe established the multicenter SAKURA AF Registry to support prospective observational research on the status of anticoagulation treatment, especially with DOAC, for AF in Japan. We enrolled 3266 AF patients treated with warfarin (n=1577) or any of 4 DOACs (n=1689) from 63 institutions (2 cardiovascular centers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 20 publications
9
72
0
5
Order By: Relevance
“…In the present study, 42.7% of the patients received 2.5 mg BID apixaban. This frequency was similar to that in Japanese registration studies (40.4% and 44%), but lower than that in a Japanese claims database study (60.6%).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, 42.7% of the patients received 2.5 mg BID apixaban. This frequency was similar to that in Japanese registration studies (40.4% and 44%), but lower than that in a Japanese claims database study (60.6%).…”
Section: Discussionsupporting
confidence: 79%
“…A recent subanalysis of the J‐RHYTHM Registry suggested that patients with lower CHADS 2 scores benefit from anticoagulation, which might lead to the prescription of rivaroxaban for such patients. Compared with the XAPASS, the percentage of patients with a CHADS 2 score of 0 or 1 was higher in other AF registries such as the J‐RHYTHM Registry (49.6%) and the SAKURA AF Registry (43.3%) . This might be explained by the fact that the Japanese guideline recommends rivaroxaban for high‐risk patients with a CHADS 2 score of ≥2.…”
Section: Discussionmentioning
confidence: 83%
“…Real‐world studies demonstrated that low doses of dabigatran and edoxaban are preferentially prescribed and their inappropriate low dosing (ILD) is greater than appropriate low dosing. This trend towards the use of ILD may be due to the reported evidence of the effectiveness of both drugs at low doses …”
Section: Resultsmentioning
confidence: 99%
“…(C) Real‐world studies results concerning dose adjustments of apixaban. (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness…”
Section: Resultsmentioning
confidence: 99%